Relationship Between Performance of the FUNDEB Municipal Board and Active and Passive Waste - Nálbia de Araujo Santos; Luana Aparecida Pereira; Daniele Silva Rodrigues (BBR: Brazilian Business Review)
This research verifies the relationship between the lack of action of the FUNDEB Monitoring and Social Control Councils with the indicators of active waste (corruption) and liabilities (mismanagement). The main sources of data used were CGU's audit reports and the websites of FNDE, IBGE and UNDP. The sample is composed of 173 municipalities supervised by the auditors of the CGU, drawn in the 38th, 39th and 40th public draws. The methodological strategies used were the content analysis and the regression for count-data, based on the negative binomial model by maximum likelihood. The results indicated a positive and significant relationship between the lack of action of the FUNDEB Monitoring and Social Control Council and the waste of public resources allocated to basic education related to poor management. This result has a general implication in evaluating the effectiveness of the FUNDEB Control Council's audit function, in accordance with its attributions established by the government’s policies and norms.